MATH SOLVE

2 months ago

Q:
# Using completing the square to solve for x in the equation (x-12)(x+4)=9

Accepted Solution

A:

Hello!

You can multiply (x-12) and (x+4)

x * x = x^2

x * 4 = 4x

-12 * x = -12x

-12 * 4 = -48

Now we have

x^2 - 8x - 48 = 9

Subtract 9 from both sides

x^2 - 8x -57 = 0

Use the quadratic formula

This give use the answer of

x = 4 +[tex] \sqrt{72} [/tex]

Hope this helps!

You can multiply (x-12) and (x+4)

x * x = x^2

x * 4 = 4x

-12 * x = -12x

-12 * 4 = -48

Now we have

x^2 - 8x - 48 = 9

Subtract 9 from both sides

x^2 - 8x -57 = 0

Use the quadratic formula

This give use the answer of

x = 4 +[tex] \sqrt{72} [/tex]

Hope this helps!